On the object of rhetoric - Gómez Posada, Julder Alexander (Estudios de Filosofía, 2010)
In regard to the discourse that studies Rhetoric the following matters are considered: Which Ontology is presupposed by a search for the Objective Conditions of Possibility of Rhetorical Discourse? And, are there conditions of this sort? Are there in things themselves of which Rethorical Discourse treats an explanation for the partial character of it? For the first question, the article refers to the Ontology of Institutional Facts developed by J. Searle. To sustain that the answer to the second question is a positive one we take our bearing in the studies on Rhetoric by Ch. Perelman.